A bibliometric analysis of verbal harassment - Maulana, Maulana; Fibiolaa, Khofifah Irya; Yurismasari, Heidi; Sununianti, Vieronica Varbi; Sartika, Diana Dewi; Santoso, Anang Dwi (International Journal of Communication and Society, 2025)
The objective of this study is to examine the scholarly literature on verbal harassment. With the aid of VOSviewer, a dataset of 145 records was extracted from the Scopus database for study. The articles were categorized by year, publication, author, co-author nation, affiliation, keywords, and journal-title. In addition, they were evaluated based on a variety of factors, including State Contributions, Institutions and Authors, Journal Distribution, Most-Cited Articles, Coupling Bibliography, and Keyword Analysis. This study identifies a number of research clusters, including discrimination, transgender, victimization, and Asian Americans, violence, sexual violence, and transphobia, as well as bullying, youth, school environment, and LGBTQ. In addition, the United States, the United Kingdom, and Canada have contributed the most to publications on the subject of verbal harassment between 1967 and 2022. The University of Minnesota, the University of California at Davis, and New York University are the three universities with the highest number of Citations in Published publications.Â